Pelatihan dan Pengembangan Sumber Daya Manusia Bidang Pendidikan : Optimasi Kemampuan Guru di Era Teknologi Canggih dan Kecerdasan Buatan (AI) - Yusrifah Rachmawati; Ida Rindaningsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The era of artificial intelligence (AI) has had a significant impact on various aspects of life, including the world of education. Amidst these changes, the role of teachers as the main agents in learning becomes very crucial. In order to optimally utilize the potential of AI, teachers need to develop their abilities in mastering technology, especially those related to AI. This journal discusses the importance of training and developing teacher abilities in mastering technology in the AI ​​era, with a focus on efforts that can be made to improve digital skills and teacher adaptation to new technologies. Through a workshop-based training approach, distance learning, and collaboration between educational institutions and technology developers, teachers can be more effective in utilizing AI to create more innovative, personalized, and effective learning experiences for students. Although challenges such as lack of time, limited access to technology, and resistance to change still exist, appropriate solutions can help teachers overcome these obstacles. This study provides recommendations for continuously improving the quality of teacher training, providing supportive infrastructure, and increasing teacher motivation in integrating AI into their learning practices. Thus, training and developing teacher abilities in the era of artificial intelligence are key to creating more advanced and relevant education in the future.